Roosevelt : the party leader, 1932-1945 - Savage, Sean J., 1964- (The University Press of Kentucky, 2015)
FDR -- the wily political opportunist glowing with charismatic charm, a leader venerated and hated with equal vigor -- such is one common notion of a president elected to an unprecedented four terms. But in this first comprehensive study of Roosevelt's leadership of the Democratic party, Sean Savage reveals a different man. He contends that, far from being a mere opportunist, Roosevelt brought to the party a conscious agenda, a longterm strategy of creating a liberal Democracy that would be an enduring majority force in American politics. The roots of Roosevelt's plan for the party ran back to.